Metamaterial enhancement of metal-halide perovskite luminescence - Adamo, Giorgio (2021)
Metal-halide perovskites are rapidly emerging as solution-processable optical materials for light-emitting applications. Here, we adopt a plasmonic metamaterial approach to enhance photoluminescence emission and extraction of methylammonium lead iodide (MAPbI3) thin films based on the Purcell effect. We show that hybridization of the active metal-halide film with resonant nanoscale sized slits carved into a gold film can yield more than 1 order of magnitude enhancement of luminescence intensity and nearly 3-fold reduction of luminescence lifetime corresponding to a Purcell enhancement factor of more than 300. These results show the effectiveness of resonant nanostructures in controlling metal-halide perovskite light emission properties over a tunable spectral range, a viable approach toward highly efficient perovskite light-emitting devices and single-photon emitters.